Grounding evaluation capacity development in systems theory. (April 2022) - Klier, Sarah D.; Nawrotzki, Raphael J.; Salas-Rodríguez, Nataly; Harten, Sven; Keating, Charles B.; Katina, Polinpapilinho F.
While "systemic thinking" is popular in the context of capacity development and evaluation, there is currently a lack of understanding about the benefits to employing systems theory in evaluation capacity development. Systems theory provides a useful orientation to the work involved in complex systems (e.g. national evaluation systems). This article illustrates how evaluation capacity development practitioners can use systems theory as a conceptual tool to gain a better understanding of the functional aspects and interrelationships present within a given evaluation system. Specifically, the systems theory perspective can help elucidate the reasons for the success or failure of a given evaluation capacity development program or activity. With the goal of motivating evaluation capacity development practitioners to use systems theory in their work, this article presents a systems theory framework for evaluation capacity development and offers practical examples of how it can be adopted.